Os significados da religiosidade na vivência de situações de stress e burnout - Yazbek, Simone (2009)
The aim of this master s thesis is to comprehend, based on the phenomenological method, the meanings of religious experience in situations of stress and burnout. In order to reach this purpose, some interviews were made with professionals working for companies in supervisory positions or above this, people who actively participate in solving problems or even as members of the team for resolution of these occurrences in the company. The analyses of the Interviews were developed according to the authors of the Phenomenological approach and working specifically with the spiritual religious coping. This study allowed us to evidence some conclusions: the beliefs and religious practices are constitutive of a frame of reference that help people cope with adverse situations in life; when there is a positive religious coping spiritual experience of such situations is re-signified offering benefits to the practitioner; the beliefs and religious practices provide a vision of world order that gives meanings positive for the experience; beliefs and religious practices have a potential transformer and reaffirmation of the practitioners